Perbuatan Melawan Hukum oleh Pemerintah dalam Kegiatan Pengadaan Tanah Pembangunan Jalan Tol Medan-Binjai (Studi Putusan Pengadilan Negeri Medan Nomor 86/Pdt.G/2019/Pn.Mdn) - Ayu Ramadhani, Binanda; Widya Kartika, Adhitya (UNES Law Review, 2024)
as regulated in Article 61 of the Presidential Regulation of the Republic of Indonesia Number 71 of 2012 concerning the Implementation of Land Acquisition for Development in the Public Interest. However, in this case, the Plaintiff as the party who has the right does not use legal remedies in the provisions mentioned above, so the Plaintiff is deemed to have accepted the decision of the land procurement committee by law. So this matter cannot be said to be an unlawful act, because there has been no rejection of the Plaintiff's objection to the results of the Inventory and Identification of Land Acquisition for the Medan - Binjai Toll Road Section I Clearance Project. As explained in the explanation above, the unlawful act committed by Defendants I, II and III regarding violating the law was wrong, because the Plaintiff had not yet held a deliberation regarding his objection, where it was clear that the implementation of land acquisition for development was in the public interest, objections to the results of the inventory and identification were rejected, the Chief Executive of Land Procurement made minutes of rejection. However, in this case no objection has ever been raised by the Plaintiff.